2023
DOI: 10.3390/pr11102840
|View full text |Cite
|
Sign up to set email alerts
|

Modified Mixed-Integer Linear Programming Formulation Implemented in Microsoft Excel to Synthesize a Heat Exchanger Network with Multiple Utilities to Compare Process Flowsheets

Maria F. Revelo,
Pablo V. Tuza

Abstract: In the present work, a modified mixed-integer linear programming model was implemented in Microsoft Excel® and minimized using the Solver tool to obtain information to devise a heat exchanger network with multiple utilities from a set of hot and cold streams and selected utilities by hand. Regarding the mixed-integer linear programming problem, the summation of utility energy was added to the model, and this energy was equal to that from the Temperature Interval method and the Grand Composite Curve. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In order to create a heat exchanger network with numerous utilities from a collection of hot and cold streams and manually chosen utilities, a modified mixed-integer linear programming model was constructed in Microsoft Excel® and reduced using the Solver tool [18]. It was shown that the annualized cost of a heat exchanger network with multiple utilities may be less than that of a network without multiple utilities due to boiler-feed water generation and the low cost of utilities.…”
Section: Introductionmentioning
confidence: 99%
“…In order to create a heat exchanger network with numerous utilities from a collection of hot and cold streams and manually chosen utilities, a modified mixed-integer linear programming model was constructed in Microsoft Excel® and reduced using the Solver tool [18]. It was shown that the annualized cost of a heat exchanger network with multiple utilities may be less than that of a network without multiple utilities due to boiler-feed water generation and the low cost of utilities.…”
Section: Introductionmentioning
confidence: 99%